Wg and Egfr signalling antagonise the development of the peripodial epithelium in Drosophila wing discs. - Baena-Lopez, L.A.; Pastor-Pareja, J.C.; Resino, J. (Development, 2003)
Imaginal discs contain a population of cells, known as peripodial epithelium, that differ morphologically and genetically from the rest of imaginal cells. The peripodial epithelium has a small contribution to the adult epidermis, though it is essential for the eversion of the discs during metamorphosis. The genetic mechanisms that control the identity and cellular morphology of the peripodial epithelia are poorly understood. In this report, we investigate the mechanisms that pattern the peripodial side of the wing imaginal disc during early larval development. At this time, the activities of the Wingless (Wg) and Epidermal growth factor receptor (Egfr) signalling pathways specify the prospective wing and notum fields, respectively. We show that peripodial epithelium specification occurs in the absence of Wingless and Egfr signalling. The ectopic activity in the peripodial epithelium of any of these signalling pathways transforms the shape of peripodial cells from squamous to columnar and resets their gene expression profile. Furthermore, peripodial cells where Wingless signalling is ectopically active acquire hinge identity, while ectopic Egfr activation results in notum specification. These findings suggest that suppression of Wg and Egfr activities is an early step in the development of the peripodial epithelium of the wing discs.